Studies on resolution of digital holography system - Yan, Hao (2012)
Digital holography (DH) is an interferometry based quantitative phase measurement technique. It includes two processes. First a digital hologram is recorded using a CCD camera. Second numerical reconstruction is performed to determine the amplitude and phase. From the phase image, the 3D measurement of the object is possible. In this thesis, the lateral resolution, its improvement and the axial measurement accuracy of digital holography are studied. Since lateral measurement and axial measurement are based on different mechanisms, digital holography system has different lateral and axial measurement capabilities. Therefore the lateral resolution and axial measurement accuracy are analyzed individually for lensless Fresnel holography configuration. Firstly, the lateral resolution of lensless digital holography is limited by CCD specifications. Three factors contribute to this limitation, namely, pixel averaging effect within the finite detection size of one pixel, finite CCD aperture size limitation and sampling effect due to finite sampling interval. As DH system is space variant, influences of object extent on lateral resolution are also involved. Interactions of these factors on lateral resolution are investigated and presented. The lateral resolution of DH system can be determined for given parameters of these factors. The domains dominated by different factors are explained along with their accuracy. Lateral resolution performance of in-line and off-axis systems is also studied and examples of lateral resolution determination for a practical system are provided. Secondly, with the results in the lateral resolution analysis, the improvement of lateral resolution is investigated by increasing the numerical aperture of the system with aperture synthesis method. Both the lateral resolution and image field of view can be enhanced at the same time using a more general Fresnel holography setup by hologram stitching. In the experiment, the synthesis is executed by moving the compact digital holographic system in two directions. Nine holograms are recorded and stitched into one hologram. The reconstruction results show that expanding aperture can improve lateral resolution. In the last part, axial measurement errors of digital holography under the influences of different limitations are analyzed. The processes related with hologram recording are focused. Related factors are finite CCD size, pixel averaging due to the signal integral within single pixel detection size, sampling effect due to CCD camera and tilt angle between the reference and the object waves. The object placement also affects the system performance. The impacts of all the above factors on the axial measurement errors are analyzed. The influences of CCD size and object displacement on the axial accuracy are demonstrated with experiments.